A Computational Fluid Dynamics (CFD) study of an airflow in a single storey building integrated with a combined system of wind catcher and solar chimney - Khalaf, Mohammed Oudah (2018)
The biggest challenge in the 21st century is global warming,which seriously threatens humanity.The Building sector,which accounts for 40 % of global energy use and greenhouse gas emissions,plays a key role in this threat. In this regard,the effects of cooling systems can not be ignored if,together with ventilation and heating systems, they account for 60 % of the energy consumed in buildings.Passive cooling systems (natural ventilation) can be a promising alternative to reduce energy consumption,especially when using two natural ventilation systems combined together.However,there are little studies that look into the combined system between two types or more of natural ventilation systems.Therefore, this study looks into the design of the combined system of windcatcher and solarchimney for natural ventilation system with ground cooling system for a single storey building as a concept for natural ventilation system and evaluate the airflow of the system by using simulation of Computational Fluid Dynamics (CFD).The simulation models were run for different wind speeds (0.5,1,and 1.5 m/s) and 303.15 K outdoor temperature.The simulation results obtained for the temperature distributions and the airflow patterns inside the room were presented with and without windcatcher,solarchimney and corrugate heat exchanger at different outdoor wind speed.The results shows that the temperature distribution in the room decreased by using catcher,solarchimney and corrugate heat exchanger.In addition,a greater temperature reduction was obtained by using the corrugated heat exchanger.The results obtained that the corrugated heat exchanger was able to reduce the temperature of the induced air stream while ensuring that the space was adequately ventilated.Moreover the results indicates that the air velocity distribution for the room increase with the increase of wind speed.